Physical Activity in Bicuspid Aortic Valve: Balancing Cardiovascular Benefits and Aortic Risk - Kurylek, Michal; Dziegciarczyk, Anna; Kozdęba, Kacper; Bala, Alicja; Korzeniak, Seweryn; Dziegciarczyk, Andrzej; Krauze, Fabian; Chybiorz, Michał (Quality in Sport, 2026)
Bicuspid aortic valve (BAV) is the most common congenital cardiac malformation and is associated with progressive valvular dysfunction and thoracic aortopathy, including ascending aortic dilation and, less frequently, dissection. As many individuals with BAV are diagnosed in childhood or early adulthood and remain asymptomatic for long periods, questions regarding the safety of physical activity and sports participation are common. Although the cardiovascular benefits of regular exercise are well established, recommendations for patients with BAV are still largely based on expert consensus rather than robust longitudinal evidence. Available evidence suggests that individuals with BAV engage in lower levels of moderate-to-vigorous physical activity and accumulate fewer daily steps than matched controls, with inactivity increasing alongside disease severity. Psychological uncertainty about safe exercise levels may further limit participation. Importantly, current observational studies do not demonstrate an association between regular physical activity, including high training volumes, and accelerated progression of aortic dilation or valvular dysfunction in adults with uncomplicated BAV. Similarly, paediatric studies show that participation in regular physical activity or competitive sports is not associated with increased aortic diameters over mid-term follow-up. Current guidelines therefore support individualized risk stratification. In the absence of valvular dysfunction, aortic dilation, ventricular impairment, arrhythmias, or other high-risk features, individuals with BAV may safely participate in physical activity and, in selected cases, competitive sports under structured surveillance. Overall, available evidence does not support routine physical activity restriction in asymptomatic individuals with uncomplicated BAV. Exercise recommendations should be individualized, and further long-term prospective studies are needed to refine risk stratification.